The Effect of Neuroanatomic Development in Childhood and Adolescents to The Juvenile Criminal Responsibility - Yıldız, Abdulkadir (The Bulletin of Legal Medicine, 2018)
Technological and conceptual developments in recent years have enabled the establishment of the relationship between the structural and functional maturation of the adolescents brain and adolescents behavior. Diffusion tensor imaging (DTI) studies have shown that white matter in the frontal region and myelination are significantly lower in children than in adults. The construction of gray and white matter continues until early adulthood, including adolescence. The thickness and maturation of the dorsolateral prefrontal cortex, which performs impulse control, judgment, and decision making, is the region that reaches the adult level at the latest. The increase in white matter reflects the increase in myelination associated with age related cognitive processes. In adolescence, significant changes occur in the dopamine receptor concentration and distribution in the pathways between the limbic system in which emotions, reward and punishment experiences are treated and the prefrontal cortex, the chief of brain executive functions. Studies on the serotonergic system, which has significant effects on many behaviors such as mood, sleep, anxiety, impulsivity, have shown that the restructuring of serotonergic neurotransmission continues throughout childhood and adolescence. These findings indicate that many complex cognitive processes do not complete their development until early adulthood. The literature suggests that adolescents are inadequate in moral, social, legal reasoning, judgment, decision making, and impulse control, which have an important role in assessing criminal responsibility in adolescence due to neuroanatomical and neurochemical changes. When studies on the evaluation of child criminal responsibility made by the doctors in Turkey are examined, it is seen that the...
Keywords: juvenile criminal responsibility; juvenile delinquency; adolescents; neuroanatomical development